EBOLA: IMPACT AND RESPONSE : EBOLA - Alsabaani, Abdullah A.; Muzammil, Khursheed; Mahmood, Syed Esam (Indian Journal of Community Health, 2019)
Ebola virus disease (EVD) is a severe illness caused by Ebola viruses affecting man and non human primates. This Ebola hemorrhagic fever (EHF) or simply Ebola, is often deadly in nature. The virus is transmitted to man from wild animals such as fruit bats. It is thought that fruit bats of the Pteropodidae family are natural Ebola virus host and act as normal carrier in nature. The WHO affirmed the EVD outbreak as a “Public Health Emergency of International Concern” on August 8th, 2014. EVD is manifested by fever, fatigue, muscle, pain, headache, and sore throat. There is no proven treatment for Ebola. Simple interventions can significantly improve chances of survival. Supportive treatment includes rehydration with fluids and body salts.. EVD has a risk of death in those infected, between 25% and 90%. Rapid geographic dissemination, nonspecific clinical presentation, lack of vaccine, and specific diagnostic test are the possible challenges to combat this dreaded public health menace. Hand hygiene is the most effective way to prevent the spread of the Ebola virus. Ebola vaccine candidates against Ebola have been developed in the decade prior to 2014, but none have yet been approved for clinical use in humans. Most recently, the European Medicines Agency (EMA) has approved the first ever Ebola vaccine (rVSV-ZEBOV-GP vaccine). This development has been appreciated from all the corners as it is in the interest of mankind and will always be considered as an important milestone in the field of public health.